Recovery of Holothuroidea population density, community composition, and respiration activity after a deep‐sea disturbance experiment. (13th July 2018) - Stratmann, Tanja; Voorsmit, Ilja; Gebruk, Andrey; Brown, Alastair; Purser, Autun; Marcon, Yann; Sweetman, Andrew K.; Jones, Daniel O. B.; van Oevelen, Dick
Abstract: Mining polymetallic nodules on abyssal plains will have adverse impacts on deep‐sea ecosystems, but it is largely unknown whether the impacted ecosystem will recover, and if so at what rate. In 1989 the "DISturbance and reCOLonization" (DISCOL) experiment was conducted in the Peru Basin where the seafloor was disturbed with a plough harrow construction to explore the effect of small‐scale sediment disturbance from deep‐sea mining. Densities of Holothuroidea in the region were last investigated 7 yr post‐disturbance, before 19 yr later, the DISCOL site was re‐visited in 2015. An "ocean floor observatory system" was used to photograph the seabed across ploughed and unploughed seafloor and at reference sites. The images were analyzed to determine the Holothuroidea population density and community composition, which were combined with in situ respiration measurements of individual Holothuroidea to generate a respiration budget of the study area. For the first time since the experimental disturbance, similar Holothuroidea densities were observed at the DISCOL site and at reference sites. The Holothuroidea assemblage was dominated by Amperima sp., Mesothuria sp., and Benthodytes typica, together contributing 46% to the Holothuroidea population density. Biomass and respiration were similar among sites, with a Holothuroidea community respiration of 5.84 × 10 −4  ± 8.74 × 10 −5 mmol C m −2 d −1 at reference sites. Although these results indicate recovery of Holothuroidea, extrapolations regarding recovery from deep‐sea mining activities must be made with caution: results presented here are based on a relatively small‐scale disturbance experiment as compared to industrial‐scale nodule mining, and also only represent one taxonomic class of the megafauna.